The Influence of Influencer Marketing, Electronic Word of Mouth, and Brand Trust on Purchasing Decisions for Sunscreen Facetology in Generation Z in East Purwokerto - Tri Septin Muji Rahayu; Putri Rizky Aulia; Dian Widyaningtyas; Meydy Fauziridwan (Universitas Batanghari Jambi, 2026)
This study aims to determine the effect of Influencer Marketing, Electronic Word of Mouth, and Brand Trust on Purchasing Decisions for Sunscreen Facetology in Generation Z in East Purwokerto. The research instrument used a questionnaire to collect data on Generation Z in East Purwokerto. The sampling approach used was purposing sampling with a non-probability method. Data were analyzed using multiple linear regression tests. Influencer marketing (X1) has a positive but insignificant effect on piurchasing decisions (Y). Meanwhile, electronic word of mouth (X2) and brand trust (X3) have a significant positive effect on purchasing decisions (Y) for Facetology Sunscreen.